Evaluasi Kinerja Pegawai Jabatan Struktural Dengan Jabatan Fungsional Pasca Terbit Kebijakan Tunjangan Tambahan Penghasilan Di Dinas Pendidikan Kabupaten Mappi - Minipko, Kosmas Harry Wahyudi; Ferinandus Leonardo Snanfi; Sri Sediyaningsih (Dinasti Review, 2024)
The main problem in this research is that the performance of structural officials and the performance of functional officials at the Mappi District Education Office have not reached the expected targets, so the aim of this research is to analyze the influence of working conditions, work performance and workload on the performance of structural and functional officials. The sampling technique used the quota sampling method with a sample size of 100 respondents consisting of 20 structural officials and 80 functional officials. The variable measurements were carried out using Likert scale parameters. Data analysis uses descriptive statistics using SPSS to test hypotheses. The research results show: 1) working conditions have a significant effect on the performance of structural officials, 2) Work performance has a positive and significant effect on the Performance of Structural Officials, 3) Workload has a positive and significant effect on the performance of structural officials, 4) Working conditions have a negative and insignificant effect on performance of functional officials, 5) work performance has a positive and significant effect on the performance of functional officials, 6) Work load has a positive and significant effect on the performance of functional officials.